Comparison of Depth Control from Surface and Bottom Set point of an Unmanned Underwater Remotely Operated Vehicle using PID Controller - Lim , Wee Teck; Mohd Aras, Mohd Shahrieel; Ab Azis, Fadilah; Mohd Nor, Arfah Syahida; Hasim, Norhaslinda (2014)
This paper investigates the depth control of an Unmanned Underwater Remotely Operated Vehicle (ROV) based on ballast tank system using conventional PID controller. The PID Controller is applied to control the depth of the ROV from two different reference points, from the surface and from the seafloor. The concept of ballast tank system selected is piston tank type. Two different sensors are selected, which is pressure sensor for measurement from the surface, and sonar sensor for measurement from the bottom. Control method from both references point are investigated and compared to find out which feedback reference points are more appropriate in different conditions. The implementation phase will be verified through MATLAB Simulink platform. The verified algorithms will then be tested on the actual prototype ROV. And also the prospect of automated the vertical movement of a ROV.